Graduate Instruction in Political Economy - Hollander, Jacob H. (Journal of Political Economy, 1912)
who has had the individual seminar. When the investigator has run the gauntlet of his instructor, and obtained some definite results, then it is good for him and for his fellow-students to lay his performance before the group and stand fire from all possible quarters. Graduate students who have had this kind of training find, when they go to Germany, that the teaching of economics there has not advanced as far as in this country. J. LAURENCE LAUGHLIN TiiE UNIVERSITY OF CHICAGO